A novel CMOS-MEMS integrated pressure sensing structure based on current mirror sensing technique. Issue 2 (5th May 2015) - Rathore, Pradeep Kumar; Panwar, Brishbhan Singh; Akhtar, Jamil
Abstract : Purpose: – The present paper aims to propose a basic current mirror-sensing circuit as an alternative to the traditional Wheatstone bridge circuit for the design and development of high-sensitivity complementary metal oxide semiconductor (CMOS)–microelectromechanical systems (MEMS)-integrated pressure sensors. Design/methodology/approach: – This paper investigates a novel current mirror-sensing-based CMOS–MEMS-integrated pressure-sensing structure based on the piezoresistive effect in metal oxide field effect transistor (MOSFET). A resistive loaded n-channel MOSFET-based current mirror pressure-sensing circuitry has been designed using 5-μm CMOS technology. The pressure-sensing structure consists of three identical 10-μm-long and 50-μm-wide n-channel MOSFETs connected in current mirror configuration, with its input transistor as a reference MOSFET and output transistors are the pressure-sensing MOSFETs embedded at the centre and near the fixed edge of a silicon diaphragm measuring 100 × 100 × 2.5 μm. This arrangement of MOSFETs enables the sensor to sense tensile and compressive stresses, developed in the diaphragm under externally applied pressure, with respect to the input reference transistor of the mirror circuit. An analytical model describing the complete behaviour of the integrated pressure sensor has been described. The simulation results of the pressure sensor show high pressure sensitivity and a good agreement with the theoretical model has been observed. A five mask level process flow for the fabrication of the current mirror-sensing-based pressure sensor has also been described. An n-channel MOSFET with aluminium gate was fabricated to verify the fabrication process and obtain its electrical characteristics using process and device simulation software. In addition, an aluminium gate metal-oxide semiconductor (MOS) capacitor was fabricated on a two-inch p-type silicon wafer and its CV characteristic curve was also measured experimentally. Finally, the paper presents a comparative study between the current mirror pressure-sensing circuit with the traditional Wheatstone bridge. Findings: – The simulated sensitivities of the pressure-sensing MOSFETs of the current mirror-integrated pressure sensor have been found to be approximately 375 and 410 mV/MPa with respect to the reference transistor, and approximately 785 mV/MPa with respect to each other. The highest pressure sensitivities of a quarter, half and full Wheatstone bridge circuits were found to be approximately 183, 366 and 738 mV/MPa, respectively. These results clearly show that the current mirror pressure-sensing circuit is comparable and better than the traditional Wheatstone bridge circuits. Originality/value: – The concept of using a basic current mirror circuit for sensing tensile and compressive stresses developed in micro-mechanical structures is new, fully compatible to standard CMOS processes and has a promising application in the development of miniaturized integrated micro-sensors and sensor arrays for automobile, medical and industrial applications.